Factors That Influence For Nurses Who Implement Triage In The Emergency Department Hospital National Guido Valadares Dili Timor-Leste - Oqui, Maximiano; dos Santos, Julito; Soares, Miguel; Jose de Jesus Canosa Alves, Maria; Frutalegio da Costa Freitas, Aureo; da Conceição, Florinda (Jurnal Syntax Fusion, 2023)
In the world of globalization Triage is very important for use in the hospital, mainly in the emergency room, so that patients can be classified according to the triage category based on the degree of trauma or pain, in order to facilitate quick care. The research result for the researcher Kharina et all., (2020) nurses' knowledge about triage the category that is still not optimal. That this through the research result approximates 88.89% knowledge nurses less, 11.11% knowledge nurses good and 5.56% knowledge nurses moderate. According to the researcher Simões F. Laura (2022) nurses who apply triage with 67.5%, sometimes 25.0% and do not apply it to triage 7.5%. The objective of the research refers to knowing the factors that influence nurses who implement triage in the emergency department of Hospital National Guido Valadares This researcher uses quantitative method that works in emergency Unit, with a total sample of 56 people technic Sampling NonProbability Sampling is a total sampling. Data correlation techniques using the questionnaire, data analysis and using formula Spearman Rank. Of the 56 samples that have been research, knowledge is known in good category with 69.6%, the category was enough 26.8% and the category was less than 3.6%. knowledge was well understood by 60.7%, the category was enough for 23.2% and les than 2.6%. the value for the Spearman Rank test obtained p= 0.000 with a value of r= 0.509 means in relation. In the research the majority of the triage was 69.6% and the majority of the triage training was 54%. The relationship between the implementation fo the triage and the training of nurses with a significant value p= 0.000 with a value r= 0.509 means in relation.